2002
DOI: 10.1063/1.1498005
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelastic phase in SrBi2Ta2O9 and study of the ferroelectric phase-transition dynamics

Abstract: Polarized microscope observation of ferroelastic domains in a SrBi2Ta2O9 (SBT) single crystal reveals the presence of domains up to Tc1≃770 K, which supports the ferroelasticity and Amam symmetry of the intermediate phase between ferroelectric and paraelectric phases. Far-infrared spectra of SBT ceramics, single crystal and thin films show a well underdamped optical soft mode at 28 cm−1, which partially softens to 21 cm−1 near the ferroelectric transition temperature (Tc2≅600 K). This softening does not explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 18 publications
6
46
0
Order By: Relevance
“…Structural studies in polycrystalline samples showed the existence of the intermediate phase (occurring between ~ 350 and 550 o C), although its space group (Fmmm [8], Amam [9,10] or B2cb [11]) was under debate. A direct observation of ferroelastic domains which disappears about 550 o C supports the ferroelasticity and the Amam symmetry of the intermediate phase [12]. Surprisingly, SrBi 2 Nb 2 O 9 shows a single crystallographic phase transition [13] which seem to exhibit a direct phase transition from the high-temperature tetragonal to a ferroelectric phase.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Structural studies in polycrystalline samples showed the existence of the intermediate phase (occurring between ~ 350 and 550 o C), although its space group (Fmmm [8], Amam [9,10] or B2cb [11]) was under debate. A direct observation of ferroelastic domains which disappears about 550 o C supports the ferroelasticity and the Amam symmetry of the intermediate phase [12]. Surprisingly, SrBi 2 Nb 2 O 9 shows a single crystallographic phase transition [13] which seem to exhibit a direct phase transition from the high-temperature tetragonal to a ferroelectric phase.…”
mentioning
confidence: 81%
“…This is in agreement with the results of Kamba et.al. who observed a gradual disappearance of elastic domains on heating, suggesting that the transition at T c2 is near second order [12].…”
mentioning
confidence: 99%
“…Such temperature behaviour cannot explain dielectric anomaly observed in low-frequency dielectric data near T c1 , therefore the name soft mode is not correct. We proposed existence of an additional relaxation mode, which will slow down to T c1 and will cause dielectric anomaly near T c1 [9]. This relaxation we really observed in recent THz spectra below 300 K [14,16].…”
Section: Introductionmentioning
confidence: 90%
“…S Second harmonic generation (SHG) signal was measured on SBT single crystal with dimensions of about 2 mm x 1mm x 0.1 mm, its large face was perpendicular to the c axis. The same crystal was used in a previous studies [9,14]. Q-switched Nd-YAG laser served as a light source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation